THE EFFECT OF USING TOTAL PHYSICAL RESPONSE STORYTELLING ON STUDENTS’ SPEAKING ACHIEVEMENT - Yenni Rofina Simanjuntak; Lince Sihombing (Universitas Negeri Medan, 2015)
This study deals with the investigation of the effect of using Total Physical Response Storytelling on Students’ Speaking Achievement. This study was conducted by using experimental research. The population of the study was the third grade of SMP N 22 Medan. There were seventy two students used as the sample out of the research taken from two classes and they were divided into two groups namely the experimental group and control group. The experimental group was taught by using Total Physical Response Storytelling while the control group taught without using Total Physical Response Storytelling. The instrument of collecting the data was an oral test. To obtain the result of the reliability of the test, the researcher used the Product Moment Formula. The result of the calculation showed that the reliability of the test was 0.63, which means that the reliability of the test is high. The data were analyzed by using t-test formula. The result of the analysis showed that tobserved is exceeded than ttable (3,692 > 1,994) at the level of significance of 0.05 with the degree of freedom (df) 70. The result of this study showed that the students’ speaking achievement taught by using Total Physical Response Storytelling is higher than those who taught without using Total Physical Response Storytelling.